1995
DOI: 10.5194/npg-2-241-1995
|View full text |Cite
|
Sign up to set email alerts
|

Successive bifurcations in a shallow-water model applied to the wind-driven ocean circulation

Abstract: Abstract. Climate - the "coarse-gridded" state of the coupled ocean - atmosphere system - varies on many time and space scales. The challenge is to relate such variation to specific mechanisms and to produce verifiable quantitative explanations. In this paper, we study the oceanic component of the climate system and, in particular, the different circulation regimes of the mid-latitude win driven ocean on the interannual time scale. These circulations are dominated by two counterrotating, basis scale gyres: sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
158
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(171 citation statements)
references
References 0 publications
13
158
0
Order By: Relevance
“…Cessi and Ierley (1995) conjecture that all equilibria are of significance in the description of the low-frequency variability of the wind-driven circulation, regardless of their stability. Comparable experiments with the primitive equations were performed by Speich et al (1995) and Jiang et al (1995). Despite the fact that the primitive equations do not satisfy quasi-geostrophic symmetry, they showed that the asymmetric equilibria come in pairs, in agreement with the quasi-geostrophic calculations.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Cessi and Ierley (1995) conjecture that all equilibria are of significance in the description of the low-frequency variability of the wind-driven circulation, regardless of their stability. Comparable experiments with the primitive equations were performed by Speich et al (1995) and Jiang et al (1995). Despite the fact that the primitive equations do not satisfy quasi-geostrophic symmetry, they showed that the asymmetric equilibria come in pairs, in agreement with the quasi-geostrophic calculations.…”
Section: Introductionsupporting
confidence: 60%
“…Beside the role played by dissipative processes within the western boundary currents, the rich structure of multiple equilibria is becoming evident. Several authors show that, for a range of parameters, the double-gyre circulation possesses multiple steady states (e.g., Cessi and Ierley, 1995;Speich et al, 1995;Jiang et al, 1995;Primeau, 1998a,b;Scott and Straub, 1998). More precisely, these authors explicitly computed fixed point solutions for a broad range of parameters except Jiang et al (1995).…”
Section: Introductionmentioning
confidence: 99%
“…These gyres have a typical horizontal scale of about one thousand kilometers. Several main features of the double-gyre ocean circulation have been identified by analyzing the observational data as well as by numerical simulations; see, for instance, Speich and Ghil [30], Jiang et al [12], and Speich et al [29]. First, these gyres are dominant and persistent; second, they represent typical seasonal and inter-annual oscillations of the large-scale ocean; third, they transfer potential energy.…”
Section: Introductionmentioning
confidence: 99%
“…Many published results are available on wind-driven ocean circulation; see, among others, Veronis [33], Pedlosky [22], Stommel [31], Charney [5], Haidvogel et al [9], Speich and Ghil [30], Jiang et al [12], Speich et al [29], Chassignet [6,7,21], Holland [10], Holland and Rhines [11], Berloff and Meacham [1,2], and Meacham and Berloff [20]. They used this model to study the formation of the western boundary currents in the North Pacific and the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…This predictability is associated with ocean dynamics and its interaction with the atmosphere (Davis, 1976;Namias, 1979;Wallace and Jiang, 1987). Recent studies (Jacobs et al, 1994;Speich et al, 1995) suggest that the intrinsic variability of North Pacific major currents may modulate and interact with the sea surface temperature (SST) anomaly signals on a decadal time scale. This may give a background of the fluctuation of precipitation.…”
mentioning
confidence: 99%